نماذج التنبؤ باحتمال قرار المستهلك السوري في التعامل بالخدمة المصرفية وفقاً لمتغير النوع - صالح خلود (Latakia University Journal - Economic and Legal Sciences Series, 2016)
There were real difficulties in marketing of the banking services in Syria, especially for possibility of dealing with this services by Syrian customer. Current research tries to build prediction models of the probability of the Syrian customer in dealing with banking services, and to study so far if there was differences between gender segments, through the use of logistic regression technique taking in consideration the decision variable takes only two values (deals, not deal) and explained this variable by variables the more power on behavior interpretation of the purchase, i.e. demographic, personal and technological ones just as indicates in literature. Study on acceptable sample performed from 976 so reply, where the tests show substantial differences between males and females in dealing with banking services. Two models for males and females was founded. Age with negative impact and education with positive impact appears clearly in both models, where technological variable related to security factors appears positive impact on the males segment, whereas personal variable related in desire and interest shows positive impact for females segment. Finally, research recommands to take in consideration this type of models by banking organizations, and to develop similar models for other type of banking services or other segments of customer. هناك صعوبات حقيقية قي تسويق الخدمات المصرفية في سورية خصوصاً لناحية احتمال تعامل المستهلك السوري بهذه الخدمات. يحاول البحث الحالي بناء نماذج للتنبؤ باحتمال تعامل المستهلك السوري بالخدمات المصرفية ودراسة فيما إذا كانت هناك فروقات بين النماذج وفقاً لشريحتي النوع، وذلك باستخدام تقنيات الانحدار اللوجستي باعتبار أن متغير القرار يأخذ قيمتين فقط (يتعامل، لا يتعامل) وشرحه بالمتغيرات الأكثر قدرةً على تفسير سلوك الشراء مثل العوامل الديموغرافية والشخصية والتكنولوجية كما تُشير إليها الأدبيات السابقة. أجريت الدراسة الميدانية على عينة مؤلفة من 976 فرداً، و بينت الاختبارات وجود فروقات جوهرية لناحية تعامل الذكور والإناث بالخدمات المصرفية، كما تم إيجاد نموذجين لكل من الشريحتين يظهر فيهما متغيرو العمر والحالة التعليمية بشكل واضح، ويُلاحظ أن معاملات تابع المنفعة تُظهر تأثيراً سلبياً للعمر وإيجابياً للحالة التعليمية لكل من الشريحيتن، كما يُظهر المتغير التكنولوجي المتعلق بعوامل الأمان تأثيراً إيجابياً لدى الذكور، في حين كان للمتغير الشخصي المتعلق بالرغبة والاهتمام تأثيراً إيجابياً لدى الإناث. ويوصي البحث باعتماد مثل هذه النماذج من قبل المؤسسات المصرفية وتطوير نماذج مماثلة لخدمات أو لشرائح أخرى.